Evaluation of different methods for determining the angle of attack on wind turbine blades with CFD results under axial inflow conditions. (September 2018) - Rahimi, H.; Schepers, J.G.; Shen, W.Z.; García, N. Ramos; Schneider, M.S.; Micallef, D.; Ferreira, C.J. Simao; Jost, E.; Klein, L.; Herráez, I.
Abstract: This work presents an investigation on different methods for the calculation of the angle of attack and the underlying induced velocity on wind turbine blades using data obtained from three-dimensional Computational Fluid Dynamics (CFD). Several methods are examined and their advantages, as well as shortcomings, are presented. The investigations are performed for two 10 MW reference wind turbines under axial inflow conditions, namely the turbines designed in the EU AVATAR and INNWIND.EU projects. The results show that the evaluated methods are in good agreement with each other at the mid-span, though some deviations are observed at the root and tip regions of the blades. This indicates that CFD results can be used for the calibration of induction modeling for Blade Element Momentum (BEM) tools. Moreover, using any of the proposed methods, it is possible to obtain airfoil characteristics for lift and drag coefficients as a function of the angle of attack. Highlights: Investigation of different methods for the calculation of the AoA on wind turbine blades is presented. A detailed explanation of different methods as well as their advantages and shortcomings are presented. The evaluated methods are in good agreement with each other at the mid-span. Some deviations were observed at the root and tip regions of the blade. Results can shed light on the calibration of engineering models in BEM.